P16INK4a/Ki-67 dual stain cytology for cervical cancer screening in Thika district, Kenya - Wangari Ngugi, Caroline; Schmidt, Dietmar; Knebel Doeberitz, Magnus von; Reuschenbach, Miriam (Infectious agents and cancer, 2015)
Background: The identification of suited early detection tests is one among the multiple requirements to reduce cervical cancer incidence in developing countries. Methods: We evaluated p16INK4a/Ki-67 dual-stain cytology in a screening population in Thika district, Kenya and compared it to high-risk human papillomavirus (HR-HPV) DNA testing and visual inspection by acetic acid (VIA) and Lugol’s iodine (VILI). Results: Valid results for all tests could be obtained in 477 women. 20.9 % (100/477) were tested positive for HR-HPV DNA, 3.1 % (15/477) had positive VIA/VILI and 8.2 % (39/477) positive p16INK4a/Ki-67 cytology. Of 22 women that showed up for colposcopy and biopsy, 6 women were diagnosed with CIN3 and two with CIN2. All women with CIN2/3 were negative in VIA/VILI screening and positive by HR-HPV DNA testing. But HPV was also positive in 91.7 % (11/12) of women with normal histology. p16INK4a/Ki-67 cytology was positive in all 6 women with CIN3, in one of the two CIN2 and in only 8.3 % (1/12) of women with normal histology. Conclusions: p16INK4a/Ki-67 cytology is an interesting test for further studies in developing countries, since our findings point to a lower fraction of false positive test results using p16INK4a/Ki-67 cytology compared to HPV DNA testing in a Kenyan screening population. VIA/VILI missed all histology-proven CIN2/3.